Efeito do ultrassom de alta potência sobre a qualidade do músculo bíceps femoris de bovinos da raça nelore - Schuch, Alexia Francielli (2017)
In relation to beef, tenderness is one of the most required attributes by consumers. Therefore, tenderness techniques applied in low tenderness meat cuts allow to aggregate value of the directlyto these cuts. Ultrasound treatment, an emergent technology, has been an alternative proposed to tenderness increase in low tenderness meat cuts, as Biceps femoris bovine muscle. In this research, the aim was to evaluate the ultrasound effects on quality of Biceps femoris muscle from Nelore bovines using ultrasound-bath by response surface methodology (RSM). A central composite rotational design (CCRD) 22 with triplicate in central point (11 assays) was used to ultrasound treatment in Biceps femoris 24 h post-mortem. Ultrasound power (x1) and time (x2) were the independents variables. Dependents variables () were Warner-Bratzler shear-force (SF), water loss, pH, color (L*, a* and b*), and water holding capacity (WHC). SF decrease was used as parameter to identify the optimum condition. Samples sonicated in optimum condition were compared with control samples by analysis of lipid oxidation (TBARS), sarcoplasmic calcium content, myofibril fragmentation index (MFI), and fatty acid profile. All analytical determinations were performed in 24, 72 and 144 h after ultrasound treatment. In CCRD, x2 linear term was significant statistically (p ≤ 0.05) to SF decrease in Biceps femoris bovine muscle. RSM allowed noting that ultrasound application with 22.6 w cm-2 ultrasound power and 120 s resulted in lower SF value, characterized as optimum experimental condition. The results of pH, color (L*, a* and b*), WHC, water loss and TBARS in sonicated samples in optimum condition were not different (p > 0.05) of control samples. These results pointed that ultrasound treatment did not affect lipid oxidation of beef until 144 h. Sonicated samples exhibited higher sarcoplasmic calcium content (p ≤ 0.05) than control. However, MFI—indirect measure of calpain proteolytic activity— was not different (p > 0.05) between sonicated samples and control. This result suggests that SF decrease could have been result from collagen changes and did not from z-line protein degradation. In fatty acid profile, the sums of monounsaturated fatty acids and polyunsaturated fatty acids were higher (p ≤ 0.05) in sonicated samples than control, and the inverse was observed to saturated fatty acids sum. These results demonstrated that ultrasound treatment contributed to phospholipid cellular membrane rupture and consequent release of unsaturated fatty acids. Ultrasound treatment did not affect negatively the beef quality parameters and contributed to tenderness increase as 24% of SF decrease in relation to control samples.